Binding Ties of Miscegenation and Identity: The Narratives of Henrique Senna Fernandes (Macao) and Rex Shelley (Singapore) - Morais, Isabel Maria Da Costa (Portuguese and Luso-Asian Legacies in Southeast Asia, 1511–2011, vol. 1: The Making of the Luso-Asian World: Intricacies of Engagement, 2011)
Vários “pequenos” portugueses fizeram sentir a sua presença na “imensa Asia”, uns quase como reis, alguns como escravos, o maior número simplesmente como portugueses capazes de amar mulheres orientais e ser por elas amados. Capazes de fecundar mulheres de cor e fazer sair dos seus ventres portugueses também de cor.(Several “small” Portuguese made felt their presence in the “enormous Asia”, some as almost kings, others as slaves, the great majority just as Portuguese [who were] able to love oriental women and be loved by them. [They were] able to inseminate women of colour and to make their wombs produce other Portuguese also of colour.)Gilberto Freyre, Aventura e RotinaDespite the dynamics of globalization and rapid economic and political development, it is still noticeable nowadays that several Portuguese creolized communities in postcolonial societies have resisted cultural homogenization, particularly those scattered throughout the detached, peripheral regions of East and Southeast Asia that were under the Estado da Índia's sovereignty and influence (Goa, Daman, Diu, Sri Lanka, Malacca, Macao and Timor) and that the Portuguese created alongside the local political authorities (Indonesia and today's Singapore).By the beginning of the seventeenth century, the official population in the colonies of several territories in Asia that proudly claimed Portuguese ancestry had reached nearly one-and-a-half million individuals, as a legacy of colonial (dis)encounters. Centuries later, the Portuguese descendants of this “shadow empire” forged through trading, matrimonial alliances and cultural networks — notwithstanding a pragmatic adaptation to times of unprecedented political, economic and cultural upheaval — persist in a quest for identity and cultural reaffirmation of “Portuguese” cultural differentiation, which continues to be faithfully perpetuated and transmitted, centuries after the earlier Portuguese contacts ceased. These communities show distinctive aspects of what could be called a certain “Luso-Eurasianness”, exhibited in oral literature, religious practices, family surnames, ceremonies, cuisine, public structures, ways of speaking and, above all, in identity-making religious and cultural reinterpretation of lived and shared commonalities.This study argues that, even if relatively scant attention has been paid to the literary production of the communities considered here, in particular in Anglophone postcolonial studies, they have influenced and continue to exercise seminal influence on most postcolonial imaginaries, either in their respective societies or in the contemporary fiction of the Luso diaspora.

A proposal for a revitalization plan for camoes area in Macao and its surrounding community through a humanistic approach - Lei, Mei Kei (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The neglected heritage of the religious resources in Macao SAR: a feasibility study on developing religious tourism - Wong, Ka Lai (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

O Sonho e o Desejo Libertários da "Lusa Macaense" Lee Li-Lyang: O Heterónimo Feminino na poética de Virgílio De Lemos", - Morais, Isabel Maria da Costa (Entre a Desmistificação e a utopia: Indagação sobre as Lusofonias , Macau: University of Saint Joseph.69-95, 2014)
Virgílio de Lemos (1929-2013), poeta de vanguarda, é um dos precursores da modernidade e experimentalismo como criador do “barroco estético” que ele próprio designou como a linguagem poética marcante nas letras moçambicanas no das décadas de 50 e 60

The tortuous route of the street hawkers in Macao: tales of persistence from the 1950’s to 2015 - Kam, Pui Han (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

A symbologia Chinesa nos contos de antonio torrado: uma breve abordagem a recepcao da literatura infanto-juvenil em Macau e na China - Fong, Mei Ian (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph